Preparation, characterisation and evaluation of polymeric thin film from kojic monooleate nanoemulsion for cosmetic application - Mohd Jaslina, Nur Farzana Izzati (2021)
A derivative of kojic acid, kojic monooleate (KMO) contains tyrosinase inhibitor and exhibits strong antioxidant activity makes it a good candidate to be incorporated into a formulation for cosmetic application. Recent developed formulation containing KMO formed a sticky, fragile and easy to fall-off thin film on the skin, in order to counter the problem, thin film system (TFS) was introduced and incorporated into the formulation. In this study, an oil in water (O/W) nanoemulsion formulation in thin film system (TFS) containing KMO as a sole active ingredient was developed. TFS was chosen to ensure better hydration effect and penetration of KMO into the skin. TFS was developed by adding the best plasticiser and solvent at optimum percentage. The nanoemulsion was developed by using high and low energy emulsification technique. Response surface methodology (RSM) was used to optimise and analyse the effect of three variables on droplet size as a response. The optimised KMO nanoemulsion in TFS with desirable criteria was PVA (27.61% w/w), PG (1.05% w/w), and shear rate (8656.17 rpm) with predicted droplet size (110.21 nm) and actual droplet size (105.93 nm) with a residual standard error (RSE) of < 2.0% was obtained. The statistical analysis was performed by ANOVA which indicated good correlation of experimental parameters. The physicochemical properties (Zeta potential -37.37 mV, PDI 0.13, pH 4.74, viscosity 0.1058 Pa.s and heterogenous distribution) and its stability of the KMO nanoemulsion in TFS under centrifugal force and stability study for 28 days at 4 different conditions (4°C, 25°C exposed to sulight, 25°C protected from sunlight and at 45°C) showed physical properties for cosmeceutical applications. The optimised KMO nanoemulsion in TFS also shows the desired criteria of TFS with flexible and peelable characteristics, non-sticky, and short drying time of approximately 8 ± 0.13 min and this shows suitability for topical application as peeling mask. KMO nanoemulsion in TFS also disports 79.99 ± 2.53 % released of KMO across the cellulose acetate membrane after 180 min of study time. In addition, the KMO nanoemulsion in TFS was proven to be less toxic as the LC50 of KMO nanoemulsion in TFS was found to be at 50.12 mg/mL at 72hpf and 0.63 mg/mL at 96hpf and 120hpf. The results of the hydration effect of KMO nanoemulsion in TFS towards human volunteer’s skin suggesting that the KMO nanoemulsion in TFS does increase hydration of skin by 12.33% due to occlusive effect of KMO. In short, KMO nanoemulsion in TFS shows an increment of water content on skin and the penetration rate of KMO.